Prototype of domestic application for the monitoring of water distribution systems based on internet of things (Research, Society and Development, 2020)
Urban and rural water distribution systems have complex interactions between quantitative and qualitative water monitoring aspects. Such models still lack greater accuracy in providing real-time measurements and the impacts of their distribution on pipe networks over time. A loss estimation and location is one aspect that can be assessed through data acquisition methods using sensor networks and the Internet of Things (IoT) framework. This work developed an application prototype for the residential monitoring of water consumption using the ESP32 microprocessor, obtaining and analyzing measurement data over five months of observation, using statistical analysis tools to identify residential human consumption profiles and possible failures in distribution network. Nine water consumption points were monitored, where the sink for washing dishes had the highest consumption, followed successively by the shower in the bathroom suite, toilet in the bathroom suite, sink washing dishes, restroom toilet, restroom shower, washing machine, bathroom sink, and bathroom sink of the social toilet. The data were compared with the literature to assess peculiarities of our research and a path for the evolution of our application in future works.